O passado ressignificado em Respiração artificial, de Ricardo Piglia, e Em liberdade, de Silviano Santiago - Testa, Letycia Fossatti (2019)
Postmodernism, a literary part of contemporary literature, has found in Latin America several followers of its aesthetics that have discovered in it an innovative way of expressing the historical and the contemporary reality of their nations and, consequently, of the continent that they belong. Two examples are; Respiração Artificial (1980), by the Argentinean Ricardo Piglia, and Em liberdade (1981), by the Brazilian Silviano Santiago, objects of this research, which reveals a postmodern language full of social and political criticisms in relation to the historical past of their nations and, at the same time, representing the production and reception moment of these narratives. So, the objective of this research was to analyze, in the perspective of the comparative literature theory, the convergence points in the narratives and the possible dialogues between them, also the extradiegetic and intradiegetic context represented and, mainly, verifying how and through which linguistic strategies the writers represent their nations and continents history. For this, the theoretical basis were the contributions of this following names: Sandra Nitrini (2015), Tânia Franco Carvalhal (2006; 2011), Eduardo Coutinho (2003; 2011), Luiz Costa Lima (1986; 1989; 2006), Benedito Nunes (1988), Antônio Esteves (1986), Zygmunt Bauman (1998), Umberto Eco (1985; 1991), Carlos Fuentes (2011), Leyla Perrone-Moisés (2016), Wander Mello Miranda (2009; 2010), among others. This analysis allowed us to reflect, although the narratives portray past periods of the history, these past periods are used as an artifice to allude metaphorically about the present period experienced by the authors, marked by dictatorial, authoritarian and violent governments. Therefore, Piglia and Santiago also show that the history often repeats itself under new covers. Because of this, there is a need for a resignification of the past, present and its discourses. These reflections are brought through many expressive resources belong to the postmodern aesthetics, such as self-referentiality, historiographic metafiction and the pastiche, that make their works more complex and labyrinthine, giving to the reader a fundamental role in the process of the meaning construction. From this point of view, Em liberdade and Respiração Artificial can reveal how much literature and historiography are discourses created by man and have relations with each other, and none of them has the monopoly on truth.